“The Role of Information Technologies in Fostering Speech Competence of Philology Students in Higher Education" (Eurasian Journal of Learning and Academic Teaching, 2025)
The article examines modern approaches to the use of information and communication technologies in teaching English in philological higher education institutions. It highlights the growing importance of the English language as an indicator of educational attainment and professional success, emphasizing the need to develop students’ speech and communicative competence through innovative pedagogical and information technologies.